First Impressions : Sefer Hasidim and Early Modern Hebrew Printing - Skloot, Joseph A., 1983- (Book collections on Project MUSE., 2023)
"In 1538, a partnership of Jewish silk makers in the city of Bologna published a book entitled Sefer Ḥasidim, a compendium of rituals, stories, and religious instruction that primarily originated in medieval Franco-Germany. This book tells the story of how these men came to produce such a book"--